Pengaruh Abu Tandan Kosong Kelapa Sawit Terhadap Pertumbuhan Tanaman Kedelai (Glycine max L.) - R.Almaidian. Nurrijal. Yacub; Yusmaidar Sepriani; Badrul Ainy Dalimunthe (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2022)
Soybeans continue to increase linearly from year to year, but the realized results cannot meet the demand. This study aims to determine the effect of oil palm empty fruit bunch ash on soybean plant growth (Glycine max L.). This research was conducted in the village of Aek hitetoras, Marbau sub-district, North Labuhanbatu district, North Sumatra. This research was conducted from April to June 2021. The research design used was a non-factorial randomized block design (RAK) with 4 treatments, namely J0: (Empty bunches of ash 0 grams/plant). J1 : (Empty bunches of oil palm ash 300 grams/plant). J2 : (Empty bunches of oil palm ash 600 grams/plant). J3 : (Empty oil palm bunch ash 900 grams/plant). Parameters observed were plant height, number of leaves, leaf width, stem diameter. The data were analyzed using the average test with the level of ash of empty fruit bunches of oil palm. The results showed that the best treatment was using the J3 treatment (900 grams/plant of oil palm empty fruit bunch ash). Keywords: soybean, growth, jangkos ash